O papel atual do cirurgião no tratamento do GIST - Valadão,Marcus (2009)
Recent progress in gastrointestinal stromal tumor's (GIST) treatment were responsible for changing GIST's natural history. Knowlegde acquirement of molecular mechanism-based systemic therapy gave rise to the development of targeted antineoplastic drugs capable of reaching outcomes that had never been reached before. The introduction of imatinib in the clinical practice not only changed GIST's patients survival but also shifted paradigms. However, besides all these new advances and the improved results with imatinib, the surgeon still plays a pivotal role in the management of the primary GIST tumor and even in the metastatic setting.